Notes on Edibility of Tricholoma Species - Hakan Allı; İsmail Şen (Turkish Journal of Agriculture: Food Science and Technology, 2016)
The genus Tricholoma (Fr.) Staude is important in terms of hosting edible and poisonous species. Therefore, in this study, edible and poisonous Tricholoma species are evaluated, edible and valuable species are introduced. Also, poisoning syndromes are examined and discussed.